A Comparison of the Migration of 'Spiked' and 'Intrinsic' Substances from Paper and Board into Raisins and into Tenax as a Food Simulant. (24th November 2014) - Bradley, E. L.; Castle, L.; Speck, D. R.
<x xml:space="preserve">Abstract</x> Four samples of paper and board (P/B) of a type used for packaging dry foods were subjected to migration experiments using raisins and the polymeric powder Tenax as a food simulant. The P/B samples contained only low levels of diisopropylnaphthalene (DiPN) and diisobutyl phthalate (DiBP), and so, experiments were also conducted after spiking the P/B with added model substances. These were o‐xylene, acetophenone, dodecane, benzophenone, DiPN and DiBP. Migration experiments into raisins and Tenax were conducted for 10 days at 40°C. Migration levels depended strongly on the nature of the substance. Migration from spiked P/B samples was more extensive (as a percentage of that available) than migration of intrinsic migratable substances, and so, studying spiked samples tends to be conservative. It is considered likely that this is because of binding of substances, especially aromatics with pi‐electrons such as DiPN and DiBP, to active sites on the surface of P/B fibres, resulting in non‐linear absorption isotherms. However, further work would be needed to prove this conclusively. Considering the results overall and also that raisins packed in P/B can have a shelf life of up to 1 year at ambient temperatures, the test results using Tenax as a food simulant are considered to be appropriate without application of a correction factor. Copyright © 2014 John Wiley & Sons, Ltd.